Biotically driven vegetation mosaics in grazing ecosystems: the battle between bioturbation and biocompaction. Issue 3 (30th May 2017) - Howison, Ruth A.; Olff, Han; van de Koppel, Johan; Smit, Christian
Abstract: Grazing ecosystems ranging from the Arctic tundra to tropical savannas are often characterized by small‐scale mosaics of herbivore‐preferred and herbivore‐avoided patches, promoting plant biodiversity and resilience. The three leading explanations for bistable patchiness in grazed ecosystems are (1) herbivore‐driven nutrient cycling, (2) plant‐growth–water‐infiltration feedback under aridity, and (3) irreversible local herbivore‐induced abiotic stress (topsoil erosion, salinity). However, these insufficiently explain the high temporal patch dynamics and wide‐ranging distribution of grazing mosaics across productive habitats. Here we propose a fourth possibility where alternating patches are governed by the interplay of two important biotic processes: bioturbation by soil fauna that locally ameliorates soil conditions, promoting tall plant communities, alternating with biocompaction by large herbivores that locally impairs soil conditions, and promotes lawn communities. We review mechanisms that explain rapid conversions between bioturbation‐ and biocompaction‐dominated patches, and provide a global map where this mechanism is possible. With a simple model we illustrate that this fourth mechanism expands the range of conditions under which grazing mosaics can persist. We conclude that the response of grazing systems to global change, as degradation or catastrophic droughts, will be contingent on the correct identification of the dominant process that drives their vegetation structural heterogeneity.